Prophylaxis of microelementosis in rabbits using a mixture of glauconite, succinic, humic and fulvic acids and minerals - Y. V. Korniichuk; N. H. Grushanska; V. M. Kostenko; T. A. Paliukh; I. F. Makovska (Regulatory Mechanisms in Biosystems, 2021)
Impaired metabolism of mineral substances in the conditions of industrial rabbit breeding may cause decrease in increment of live mass, reduction of immunity, mass morbidity and death of animals. In our experiment, we studied the efficiency of using a mineral mixture to prevent the disorders in the metabolism of rabbits according to changes in morphologic, biochemical parameters and antioxidant status of blood, chemical composition of blood plasma and increments in body weight compared to the control group of animals. For the studies, we formed four groups of white New Zealand rabbits, each comprising six individuals aged 70 days with mean body weight equaling 1.99 kg. In group I, the rabbits received an aqueous form of a mixture of glauconite, succinic acid, humic and fulvic acids and lactates of zinc, manganese, cuprum, cobalt and iron with water, rabbits of group II were given a dry form of a mixture of glauconite, succinic acid, humic and fulvic acids and lactates of zinc, manganese, cuprum, cobalt and iron with fodder, and the rabbits of group III were intramuscularly injected with butanol fraction of humic acids. The experiment lasted for 21 days. The results of the experiment indicate that the most effective prophylaxis of malfunctions of mineral metabolism in white New Zealand rabbits aged 70–95 was dry mixture of glauconite, succinic acid, humic and fulvic acids and lactates of zinc, manganese, cuprum, cobalt and iron with fodder (group II), which was given once a day for 21-day period. We determined a positive effect of biologically active supplement on the parameters of hematopoiesis(1.25 times significantly higher level of hemoglobin and 1.14 times higher number of erythrocytes), metabolism of proteins (1.54 times significantly higher content of albumins), mineral substances (significantly higher content of inorganic phosphorus – by 1.17 times, calcium by 2.18 times, manganese by 1.39 times, zinc by 1.50 times, iron by 1.39 times and cuprum by 1.49 times), functional condition of the liver (2.04 times lower activity of gamma-glutamyltransferase), the state of the antioxidant system (lowest catalase activity) and energy of rabbits’ growth (1.20-fold increment in body weight). The results of our study indicate that using a dry form of the mixture of glauconite, succinic acid, humic and fulvic acids and lactates of zinc, manganese, cuprum, cobalt and iron with fodder is an efficient method of preventing malfunctioning of mineral metabolism in rabbits.